UPAYA GURU TAHFIDZ DALAM MENINGKATKAN HAFALAN AL-QUR’AN SISWA KELAS X DI MADRASAH ALIYAH DARUL ‘ULUM REJOSO PETERONGAN JOMBANG - Muh. Imam Mutaqin; Nur Hasan; Khoirul Asfiyak (VICRATINA, 2020)
This research describes an effort to improve the quality of teachers in the process of improving the memorization of the Qur'an. This research will also answer two questions raised by researchers, as follows: (1) How to improve the ability of teachers to improve the memorization of Al-Qur'an class X students. (2) What obstacles are often find in an effort to improve the memorization of Al-Qur'an grade X students. This research uses descriptive qualitative. The data search in this study used three methods, observation, unstructured interviews, and documentation. The results of this research indicate that: (1) the teacher adopts the habit of each class time, the teacher applies the talaqqi, takrir, and muraja'ah methods, the teacher implements a memorization quality improvement system with the One Sitting Juz method. The teacher also gives appreciation to students who do not reach the target, and the teacher always provides motivation that is almost acceptable with learning tahfidz. (2) Obstacles to learning drowsiness, some student readings are still not in accordance with the makharijul letters and the rules of recitation, physic healts by one student because of stress on memorization targets, and a residential environment that is less representative or helps students memorize the Koran.